A Route to Terahertz Metamaterial Biosensor Integrated with Microfluidics for Liver Cancer Biomarker Testing in Early Stage. Issue 1 (December 2017) - Geng, Zhaoxin; Zhang, Xiong; Fan, Zhiyuan; Lv, Xiaoqing; Chen, Hongda
Abstract Engineered Terahertz (THz) metamaterials presented an unique characteristics for biosensing application due to their accurately tunable resonance frequency, which is in accord with vibrational frequency of some important biomolecules such as cancer biomarker. However, water absorption in THz regime is an obstacle to extend application in trace biomolecules of cancer antibody or antigen. Here, to overcome water absorption and enhance the THz biosensing sensitivity, two kinds of THz metamaterials biosensor integrated with microfluidics were fabricated and used to detect the Alpha fetoprotein (AFP) and Glutamine transferase isozymes II (GGT-II) of liver cancer biomarker in early stage. There were about 19 GHz resonance shift (5 mu/ml) and 14.2 GHz resonance shift (0.02524 μg/ml) for GGT-II and AFP with a two-gap-metamaterial, respectively, which agreed with simulation results. Those results demonstrated the power and usefulness of metamaterial-assisted THz spectroscopy in trace cancer biomarker molecular detection for biological and chemical sensing. Moreover, for a particular cancer biomarker, the sensitivity could be further improved by optimizing the metamaterial structure and decreasing the permittivity of the substrate. This method might be powerful and potential for special recognition of cancer molecules in the early stage.